Penerapan Metode Prototype dalam Perancangan Sistem Informasi Penerimaan Karyawan Berbasis Website pada Berlian Agency - Rahayu Dewi, Ni Luh Ade Mita; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2021)
This research discusses the application of the prototype method in designing a website-based employee recruitment information system. The case study used in this research is Berlian Agency, which is a business in the field of digital services that serves various needs, especially in the field of marketing such as website creation, social media management, and so on. The research carried out was adjusted to the business processes that were running at Berlian Agency, as well as by ongoing events and current conditions, therefore researchers used a descriptive method in this study. The descriptive research method is a research method that aims to describe and explain objects based on existing conditions. In this study, the development method chosen was the prototype method. The application of the prototype method makes it easier to design this system because there is a prototyping section that makes it easier for researchers to make the necessary designs. This study aims to produce an information system design for employee acceptance. Based on the research results, this system has been successfully designed as expected so that the prototype that has been made can be used as a basis for continuing to work on the system to be made. The results of this design can be used as a blueprint or documentation for the company with the hope that later it can be used as literature to develop a real employee recruitment system.